On irreducible representations of Sn - Kikwai, Benjamin K. (My University, 2009)
In chapter 1 and 2, We begin by introducing a few elementary aspects of the symmetric group Sn and there after we give a brief discussion on the representation theory with emphasis on the symmetric group. In chapter 3. we discuss the construction of an ordinary irreducible Sn-submodule basing on the lormat provided in the book bv Sagan [6]. Finally, we discuss on the lrieducibility of the constructed submodule as the base field shifts from a field of characteristic 0 to a field of characteristic p > 0